COVID-19 and field education in Australia: exploring the use of simulation. Issue 4 (2nd October 2021) - Jefferies, Gerard; Davis, Cindy; Mason, Jonathan
ABSTRACT: Given the change in social work education due to COVID-19, the use of simulation within social work field education provides a strategy to assist with skill development and training. The purpose of this study was to explore how simulation was utilised during COVID-19. A mixed-methods online survey was sent to social work academics and field educators within Australia (n = 33). Barriers to using simulation included costs, lack of expertise, technology, concerns regarding the limiting of student's real-world practice opportunities and accreditation issues. The inclusion of simulation in field education has promise in skill development and allows student exposure to complex scenarios.